Black and White mother’s beliefs and insecurity outcomes related to public assistance - Keilholtz, Brooke May (Kansas State University, 2020)
Food insecurity, housing insecurity, and financial insecurity are issues many mothers and families are facing. Low income mothers across the United States of America have access to public assistance programs to promote food, housing, and financial security. This study uses the Fragile Families and Child Wellbeing dataset to examine how Black and white mothers’ utilization of public assistance programs was associated with their experiences of food, housing, and financial insecurity and the beliefs they hold about using public assistance. Intersectionality theory, which highlights how Black mothers experience additional and unique difficulties because of they hold numerous marginalization identities, guided my research questions and implications. I found Black mothers experienced significantly higher levels of housing insecurity and financial insecurity compared to white mothers not using public assistance. In contrast, there were no significant differences in level of insecurity for Black and white mothers utilizing public assistance programs. Additionally, welfare utilization significantly moderated the relationship between financial insecurity and race. Further, any public assistance usage significantly moderated the relationship between welfare beliefs and race. Implications for mental health providers are addressed below.
Keywords: Race; Public assistance; Housing insecurity; Food insecurity; Mothers